Analysis of depression in Brazil and the feasibility of incorporating pharmacogenomics as an auxiliary tool in antidepressant treatment - Rafaela Slaviero Pinheiro Cerdeira; Mario Hiroyuki Hirata (Brazilian Journal of Pharmaceutical Sciences)
Abstract Depression has substantially increased in the last 10 years in Brazil, and mental health became a concerning issue for the public health globally, especially considering the COVID-19 pandemic. The therapeutic conduct in depression mainly relies on medication and psychotherapy. However, more than one attempt in the treatment can be considered a common procedure before finding out the right medication. This conduct leads many patients to give up following pharmacological treatment. In this scenario, pharmacogenomics emerges as a possible supporting tool of the medical treatment. This paper aims to analyze the scenario of depression in Brazil and the viability of pharmacogenomic tests implementation as a part of the medical procedure. Official data bank from the Brazilian government was used to analyze the prevalence of depressive disorder, as well as Pharmacogenomic data bases and relevant articles around this topic. Additionally, pharmacogenomic tests typically take into consideration the genes CYP2D6 and CYP2C19, which are relevant for antidepressant treatment. Data shows that these tests could help patients achieve remission of symptoms, and they could also be economically advantageous. Thus, pharmacogenomic tests present as an interesting approach for the therapeutic conduct of depression and can significantly improve the health quality of this affected population.